(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In the article, it is revealed that instilling the basics of valeology in children is the first important stage of preschool education, the main tasks of the valeological approach in preschool educational organizations, taking into account the individual characteristics of the child, and the issues of using health care technologies in preschool educational organizations